Efektivitas Bimbingan Kelompok dengan Problem Solving untuk Meningkatkan Motivasi dan Disiplin Belajar Siswa Tahfidz - Marpaung, Al Hudani; Daulay, Nurussakinah; Arsini, Yenti (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study aims to examine the effectiveness of group guidance services with problem solving techniques in increasing the motivation and learning discipline of tahfidz students in a madrasah environment. This study used a quantitative approach with a quasi-experimental design, involving 20 purposively selected students from MTs Al-Washliyah Lubuk Amat, North Sumatra. Participants were divided into two groups: experimental and control. The experimental group attended six 60-minute structured group guidance sessions designed to foster self-awareness, identify learning barriers and formulate solutions independently. The intervention was designed by integrating the spiritual values and commitment that characterize tahfidz education. Data were collected through pre-test and post-test using a Likert scale questionnaire that has been tested for validity and reliability (r = 0.456-0.986; α = 0.871). The paired sample t-test results showed a statistically significant increase in scores in the experimental group (mean difference = 24.95; p = 0.000), with a very large effect size (Cohen's d = 2.51). These findings prove that problem-solving-based group guidance is effective in supporting the behavioral and cognitive development of students who face academic and spiritual demands simultaneously. Theoretically, this study integrates Bandura's self-efficacy theory with the Islamic counseling framework. Practically, this study presents an intervention model that can be replicated in educational institutions that organize tahfidz programs. This study fills a void in the literature related to structured psychopedagogical interventions in the context of religious value-based education.